2013
DOI: 10.1103/physrevb.87.195115
|View full text |Cite
|
Sign up to set email alerts
|

Interplay among spin, orbital, and lattice degrees of freedom in a frustrated spinel Mn3O4

Abstract: We have investigated magnetic-field (H [100]) effect on a spin-frustrated tetragonally distorted spinel Mn 3 O 4 by measurements of magnetization, dielectric constant, and strain as well as synchrotron x-ray and neutron diffraction. In two low-temperature phases below 40 K, long-wavelength lattice modulations coupled with magnetic order have been confirmed, revealing spin-lattice coupling caused by the exchange striction in the geometrically frustrated Mn 3+ spin moments on the distorted pyrochlore lattice. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 15 publications
11
49
0
Order By: Relevance
“…A structural modulation with a propagation vector identical to that of the magnetic modulation has also been observed, 24 demonstrating the strong spin-lattice coupling in Mn 3 O 4 . This strong coupling is proposed to originate from the geometric frustration of the Mn 3+ spins, which is only partially relieved by the hightemperature, cubic-to-tetragonal distortion.…”
Section: 28mentioning
confidence: 73%
See 4 more Smart Citations
“…A structural modulation with a propagation vector identical to that of the magnetic modulation has also been observed, 24 demonstrating the strong spin-lattice coupling in Mn 3 O 4 . This strong coupling is proposed to originate from the geometric frustration of the Mn 3+ spins, which is only partially relieved by the hightemperature, cubic-to-tetragonal distortion.…”
Section: 28mentioning
confidence: 73%
“…13,23,24 Magneticfield-induced changes in the low-frequency dielectric constant and crystal dimensions have been attributed to field-induced transitions between two distinct magnetostructural phases, which are discussed below. 24 A highresolution x-ray diffraction study recently revealed that these two magnetostructural phases in fact coexist below the Néel temperature in polycrystalline Mn 3 O 4 , 25 demonstrating the near degeneracy of their free energies. Thus, Mn 3 O 4 belongs to the class of strongly correlated materials whose bulk physical parameters are 'tunable' due to distinct phases existing in close proximity.…”
Section: -22mentioning
confidence: 99%
See 3 more Smart Citations